Skilling Youth through Industry Linkages: Case of Nepal (Journal of Training and Development, 2019)
Nepal is in the phase of gaining its demographic dividend where more people have the potential to be productive and may contribute to achieve rapid economic growth. However, most of this productive age group lacks engagement in gainful employment both in domestic as well as international market. This paper scrutinizes the present TVET practices, identifies the gap and envisions systemic TVET implementation mechanism that ensures affordable access to TVET and a decent job for the productive age group of Nepal. The paper concludes that the linkage of industry with TVET, where industry plays a vital role in the implementation ecosystem, will serve in optimum utilization of the productive age-group.